Estimasi Sumberdaya Nikel Laterit dengan Menggunakan Metode Krigging di PT. Gerbang Multi Sejahtera - Al Amin Siharis; Hadi Zulkarnain Ladianto (Universitas Halu Oleo, 2025)
This study was conducted to estimate laterite nickel resources using a spatial approach to determine the three-dimensional model of deposit distribution within the working area of PT. Gerbang Multi Sejahtera, located in South Konawe Regency, Southeast Sulawesi. The estimation was carried out using the Kriging method. The results show that the limonite zone contains approximately 3,391,000 tons of resources with an average nickel grade of 1.1%, while the saprolite zone contains around 4,213,500 tons with an average grade of 1.51%. The three-dimensional modeling was performed using a block size of 12.5 x 12.5 x 1 meters, which provides a more accurate representation of the spatial distribution of the deposits. This study is expected to contribute to mine planning and support decision-making for further exploration.